Evaluation of Academic Service Business Processes through a Business Process Improvement Approach (Case Study: Esa Unggul University Learning Administration Bureau) - Sigit Purworaharjo; Gerry Firmansyah (Budapest International Research and Critics University, 2022)
Business Process Improvement is a systematic system framework that helps an organization in advancing or improving business processes. To find out the effectiveness of business processes running in academic service processes, it is necessary to evaluate and model existing business processes. The main objective of BPI is to improve business processes and ensure issues in an organization's business processes are handled properly. The use of BPMN is a tool for describing or modeling business process diagrams based on flow chart techniques, assembled to create graphical models of business operations where there are activities and flow controls that define the work order. The results of this study are to evaluate and improve on important functions in the learning administration bureau of Universitas Esa Unggul.